Endocrine disrupting‐chemicals and biochemical recurrence of prostate cancer after prostatectomy: A cohort study in Guadeloupe (French West Indies). Issue 3 (8th April 2019) - Brureau, Laurent; Emeville, Elise; Helissey, Carole; Thome, Jean Pierre; Multigner, Luc; Blanchet, Pascal
Abstract : Previous studies have suggested that exposure to environmental chemicals with hormonal properties, also called endocrine disrupting chemicals, may be involved in the occurrence of prostate cancer (PCa). Such exposure may also influence the treatment outcome as it is still present at the time of diagnosis, the beginning of therapy, and beyond. We followed 326 men in Guadeloupe (French West Indies) who underwent radical prostatectomy as primary treatment of localized PCa. We analyzed the relationship between exposure to the estrogenic chlordecone, the antiandrogenic dichlorodiphenyldichloroethylene (DDE, the main metabolite of the insecticide DDT), and the nondioxin‐like polychlorinated biphenyl congener 153 (PCB‐153) with mixed estrogenic/antiestrogenic properties and the risk of biochemical recurrence (BCR) after surgery. After a median follow‐up of 6.1 years after surgery, we found a significant increase in the risk of BCR, with increasing plasma chlordecone concentration (adjusted hazard ratio = 2.51; 95% confidence interval: 1.39–4.56 for the highest vs . lowest quartile of exposure; p trend = 0.002). We found no associations for DDE or PCB‐135. These results shown that exposure to environmental estrogens may negatively influence the outcome of PCa treatment. Abstract : What's new? Some environmental chemicals can mimic human hormones, and may spur cancer progression. Here, the authors studied the effect of three prevalent organic chemicals on prostate cancer recurrence: the estrogenic insecticide chlordecone; DDE, a stable metabolite of DDT which has anti‐androgenic properties; and PCB‐153, which has estrogenic and anti‐estrogenic properties. No effect was associated with DDE or PCB‐153. However, those in the highest exposure quartile for chlordecone had 2‐fold increased risk of biochemical recurrence, defined as two consecutive elevated PSA measurements, after prostatectomy. These findings add to the evidence that environmental estrogens could promote cancer progression.